2008
DOI: 10.1007/s11099-008-0082-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aluminium on photosynthetic performance in Al-sensitive and Al-tolerant maize inbred lines

Abstract: Maize plant inbred lines, one Al-sensitive (B-73) and two Al-tolerant (F-2 and L-2039), were grown hydroponically in the presence of 200 µM Al. After 13 d of growth, root and shoot lengths, photosystem 2 (PS2) activity, chlorophyll (Chl) content, 5-aminolevulinic acid (5-ALA) synthesis rate, chlorophyllase (Chlase) activity, and N, Mg, Fe, and Mn contents in leaves were determined. PS2 activity and Chl content were most severely affected by Al in B-73, but F-2 was almost unaffected. This was in accordance with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
31
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 23 publications
8
31
1
2
Order By: Relevance
“…Iron, vanadium and aluminium are known to promote both lipid peroxidation (Halliwell and Gutteridge 2007;Russanov et al 1994) and pigment degradation (Wolterbeek et al 2003). V and Al are also effective inhibitors of chlorophyll biosynthesis (Madejon 2013;Mihailovic et al 2008) while Al and Fe can depress carotenoid levels in lichens (Bačkor and Fahlset 2004) and plants (Azmat and Hasan 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Iron, vanadium and aluminium are known to promote both lipid peroxidation (Halliwell and Gutteridge 2007;Russanov et al 1994) and pigment degradation (Wolterbeek et al 2003). V and Al are also effective inhibitors of chlorophyll biosynthesis (Madejon 2013;Mihailovic et al 2008) while Al and Fe can depress carotenoid levels in lichens (Bačkor and Fahlset 2004) and plants (Azmat and Hasan 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Al inhibits root growth and elongation by different mechanisms, including Al interactions within symplast, plasma membrane and cell wall (Kochian 1995, Pineros and Kochian 2001, Yang et al 2008. Several studies revealed that Al stress decreased net photosynthetic rate (PN) and chlorophyll (Chl) content in tomato (Simon et al 1994), maize (Lidon et al 1999, Mihailovic et al 2008, Citrus spp. , Chen et al 2005a, and soybean ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the nature of the geological substrates of the Sila plateau (siliceous-acidic rocks), P. furfuracea (L.) Zopf thalli showed in both cases a slight enrichment in aluminum (above 1000 µg/g dry weight), an element that when hydroponically given to inbred lines of maize resulted in an activation of chlorophyllase (Mihailovic, 2008). This enzyme promotes the first step of chlorophyll a degradation by converting it into chlorophyllide a, while in the second step chlorophyllide a changes into pheophorbide a via magnesium-dechelatase activity (Tang et al, 2000).…”
Section: Discussionmentioning
confidence: 99%